The greediest of rajahs and the whitest of clouds - Ibardolaza, Honoel; Vallesteros, Brian (Quezon City : Adarna House, 2004)
"What else could the greediest of rajahs want? He has the fattest cows, the roundest pigs, the juiciest melons, the sweetest sugar, the finest silk, and even the purest of silver and gold. Nothing else but the whitest of clouds."--Cover.
In English and Tagalog.
First Prize, Short Story for Children 2003, Don Carlos Palanca Memorial Awards for Literature
Keywords: Children's stories, Filipino